Identitas hukum nasional - Alkostar, Artidjo; Universitas Islam Indonesia. Fakultas Hukum (Yogyakarta : Fakultas Hukum, Universitas Islam Indonesia, 1997)
Indonesian law; collection of articles.
Includes bibliographical references and index.
Keywords: Law -- Indonesia